2014
DOI: 10.3389/fcimb.2014.00095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an oxygenating agent on oral bacteria in vitro and on dental plaque composition in healthy young adults

Abstract: Oral bacteria live in symbiosis with the host. Therefore, when mouthwashes are indicated, selective inhibition of taxa contributing to disease is preferred instead of broad-spectrum antimicrobials. The potential selectivity of an oxygenating mouthwash, Ardox-X® (AX), has not been assessed. The aim of this study was to determine the antimicrobial potential of AX and the effects of a twice-daily oral rinse on dental plaque composition.Material and methods: In vitro, 16 oral bacterial strains were tested using ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…This could be explained by the selective inhibition properties of this oxygenating compound [7]. This is further supported by the observation that after AX treatment the relative abundance of genus Veillonell a was significantly lower in the treated biofilm accompanied with the higher relative proportion of other genera mainly Streptococcus .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This could be explained by the selective inhibition properties of this oxygenating compound [7]. This is further supported by the observation that after AX treatment the relative abundance of genus Veillonell a was significantly lower in the treated biofilm accompanied with the higher relative proportion of other genera mainly Streptococcus .…”
Section: Discussionmentioning
confidence: 75%
“…This could explain in part, why in a previous clinical study we observed different changes in bacterial composition after twice-daily exposures for a week to AX [7]. Oxygenating agents such as AX are on the market while scientific evidence for their use is underreported [4].…”
Section: Discussionmentioning
confidence: 97%
“…Since previous reviews [2,3], Leptotrichia species have been reported in >124 cases [4,7,16,1869,8793], whereby 30 cases involved L. buccalis [4,8,15,21,34,52,56,70–79,87], 24 cases L. wadei [4,20,24,34,37,42,48,56,67,80,81,90,93], 16 cases L. trevisanii [4,5,9,10,13,14,17,37,87], 14 cases L. hofstadii [34,40,49,56,8184,93], 10 cases L. goodfellowii [4,11,12,21,56,74,85,87], eight cases L. hongkongensis [4,6,18,45,47,56], and five L. shahii [34,56,86]. L. trevisanii and L. wadei bacteremia are extremely rare; clinicians should consider these species in cases involving immunocompromised patients with oral lesions [4,5,13,17,87].…”
Section: Figurementioning
confidence: 99%
“…L. hongkongensis has been isolated from the blood of metastatic breast carcinoma (MBC) patients [6], the blood and amniotic fluid of a patient with a wound and respiratory difficulties [4], plaque from dental caries [45,47,56], saliva from pancreatic cancer patients and black pigmented stain caries patients (Table 2) [18,63]. …”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%
See 1 more Smart Citation